Morphology of Graphene Aerogel as the Key Factor: Mechanical Properties Under Tension and Compression - Elizaveta Rozhnova; Julia Baimova (Gels)
Graphene aerogels with high surface areas, ultra-low densities, and thermal conductivities have been attracted a lot of attention in recent years. However, considerable difference in their deformation behavior and mechanical properties lead to their poor performance. The problem can be solved by preparing graphene aerogel of given morphology and by control the properties through the special structure of graphene cells. In the present work, molecular dynamics simulation is used to overview the mechanical properties of four different morphologies of graphene aerogel: honeycomb, cellular, lamellar and randomly distributed graphene flakes. All the structures are considered under uniaxial compression and tension with the detailed analysis of the deformation behavior. It is found that cellular structures have much better compressibility and elasticity. During both compression and tension, cellular structures can be transformed from one to another by controlling the compression/tensile direction. The highest strength and fracture strain are found for the lamellar GA under tension along the direction perpendicular to the alignment of the graphene walls. This reveals that the mechanical properties of graphene aerogels can be controlled by enhancing the structural morphology. The obtained results is the contribution which provide the insights into recent developments concerning the design of carbon-based structures and their application.